2021
DOI: 10.3390/app11188788
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Electricity Generation Technologies to Reduce Carbon Dioxide Emissions in Egypt

Abstract: In February 2016, the Egyptian government introduced Egyptian Vision 2030. An important pillar of this vision is energy. Egyptian Vision 2030 presented renewable energy as the best solution to reduce the emission of greenhouse gases (GHGs) in the energy sector. Egypt’s electricity comes from various power plants; conventional thermal plants generate over 90% in which gas-fired generation accounts for 75% of the total output. Following the increase in natural gas (NG) projects in Egypt, NG is the dominant elect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…Nuclear and gas power plants were shown to be long-term electricity suppliers. However, the research concluded that nuclear power plants are the best long-term alternative source of electricity generation for Egypt to fulfil future demand [84].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Nuclear and gas power plants were shown to be long-term electricity suppliers. However, the research concluded that nuclear power plants are the best long-term alternative source of electricity generation for Egypt to fulfil future demand [84].…”
Section: Discussionmentioning
confidence: 99%
“…Most research articles asserted that nuclear energy is the most reliable option for achieving national and regional CO 2 emission mitigation targets while meeting the energy supply need [81,82,84,88,89]. Furthermore, along with the rapid increase of emerging industrialized countries, the global geography of the development of nuclear energy is undergoing a spatial reconfiguration phenomenon, as indicated by studies on research and collaboration among nations.…”
Section: Nexus Between Nuclear Energy Generation and Thementioning
confidence: 99%
See 2 more Smart Citations
“…In addition, there are a number of publications on related topics, providing the readership with useful details about GHG emissions in Serbia in general [27,28], CO 2 emissions from various types of coals used in Serbian CPPs [29,30], climate change policies and plans relating to the Southeast European countries [31,32], renewable energy development trends in Serbia and the other Western Balkan countries [33,34], and so on. Moreover, some papers deal with CPPs and/or NGPPs in other countries and regions of the world, namely: India [35], Germany [36], Turkey [37], Algeria [38], Asia-Pacific [12], Southeast Asia [39,40], South Korea [41], Egypt [42], etc. Accordingly, there is no paper reviewing the potential effects of the Balkan Stream pipeline on CO 2 emissions in Serbia, reviewing planned NGPPs in Serbia, or dealing with possible scenarios and necessary measures for reducing CO 2 emissions in Serbia by the end of 2050 (by means of natural gas-fired electricity generation).…”
Section: Introductionmentioning
confidence: 99%